The interaction in sorbitol-plasticized starch bionanocomposites via positron annihilation lifetime spectroscopy and small angle X-ray scattering - Liu, Huihua; Chaudhary, Deeptangshu; Roberts, J.; Weed, R.; Sullivan, J.; Buckman, S. (Elsevier, 2012)
We investigated the free volume variations (size and distribution) within sorbitol plasticized high amylose bionanocomposites of different formula where the interactions among sorbitol, amylose and hydrophilic montmorillonite nanoclay (MMT) modified the crystallinity and therefore, the free volume of the matrix. Positron Annihilation Lifetime Spectroscopy (PALS) is a useful technique to monitor the changes of free volume within the polymer matrix – due to polymer–plasticizer or polymer–polymer interactions. In a recent investigation (Liu et al., Carbohydrate Polymer, 2011, 85(1), 97–104), we demonstrated that there exists a threshold plasticizer concentration – above which the matrix crystallinity and moisture content can be significantly altered. By investigating the relationship between the changes of free volume and the development of crystalline morphology, we presented evidence that, at the molecular level, the free volume changes due to amylose–MMT interactions were affected by the concentration of the sorbitol plasticizer. The free volume analysis revealed that when the concentration of sorbitol was low (5 wt%), the bionanocomposite showed a bimodal distribution for free volume pore-size. As the sorbitol concentration increased, these free volume pores coalesced. Further, due to sorbitol's hydrophilic nature, this study also presented the evidence of moisture ‘lock-in’ within the bionanocomposites matrix; only one pore size – was confirmed in the high moisture content samples; meaning that sorbitol was able to have binary interactions with the amylose and with the water molecules so that the free volume pore-size was relatively more uniform.